Exploring Options to Improve the Supplemental Nutrition Assistance Program (SNAP). Issue 1 (November 2019) - Schanzenbach, Diane Whitmore
The Supplemental Nutrition Assistance Program (SNAP), previously known as the Food Stamp Program, is a cornerstone of the U.S. safety net. SNAP provides means-tested electronic vouchers that can be used to purchase most foods at participating retail outlets and helps low-income families afford the food that they need. It also helps to stabilize the economy in fiscal downturns, because more benefits are paid when jobs and income are scarce. SNAP households range widely in their demographic characteristics, from those with elderly or disabled members, to prime-age families (typically with children) who combine work and benefit receipt, to those with no or very low levels of income. Potential reforms, such as policies to encourage work or improve dietary outcomes, may have different impacts on various subgroups and should be designed with the heterogeneity of the caseload in mind. I review the theoretical and empirical research literature on SNAP's impacts and consider potential reforms by analyzing them in terms of the program's stated goals.